Task-specific robot base pose optimization for robot-assisted surgeries - Sundaram, Ashok M.; Budjakoski, Nikola; Klodmann, Julian; Roa, Máximo A. (Frontiers in Robotics and AI, 2022)
Preoperative planning and intra-operative system setup are crucial steps to successfully integrate robotically assisted surgical systems (RASS) into the operating room. Efficiency in terms of setup planning directly affects the overall procedural costs and increases acceptance of RASS by surgeons and clinical personnel. Due to the kinematic limitations of RASS, selecting an optimal robot base location and surgery access point on the patient is essential to avoid potentially critical complications due to reachability issues. To this end, this paper proposes a novel versatile method for RASS setup and planning based on robot capability maps (CMAP). CMAPs are a common tool to perform workspace analysis in robotics, as they are in general applicable to any robot kinematics. However, CMAPs have not been completely exploited so far for RASS setup and planning. By adapting global CMAPs to surgical procedure specific tasks and constraints, a novel RASS capability map (RASSCMAP) is generated. Furthermore, RASSCMAPs can be derived to also comply with kinematic access constraints such as access points in laparoscopy. The method is evaluated in two different use cases, namely pedicle screw placement in vertebral fixation procedures and general laparoscopy. RASSCMAPs are versatile and applicable to any kind of surgical procedure; they can be used on the one hand for aiding in intra-operative experience- based empirical system setup by visualizing online the robot’s capability to perform a task. On the other hand, they can be used to find the optimal preoperative setup by applying a multiobjective optimization based on a genetic algorithm. The proposed RASSCMAPs aide then in increasing the overall clinical value of RASS by reducing system setup time and guaranteeing a proper robot reachability to successfully perform the intended surgeries.